THE EFFECTS OF PATRIARCHY SYSTEM ON WOMEN CONDITION IN THE NOVEL OF THE TENANT OF WILDFELL HALL - Fhadli Noer (Pusat Pengembangan Bahasa IAIN Tulungagung, 2016)
Patriarchy system occurs in the era of Victoria and many women experience the effects of this system. The aims of the study is to describe the patriarchy system presented in the novel The Tenant of Wildfell Hall by Anne Bronte. This research was conducted with descriptive qualitative method. The data were taken from Anne Bronte’s novel, The Tenant of Wildfell Hall published by Anne Bronte in 1848. Data were collected from intensive reading of the novel and library research for resources related to patriarchy system. The result of study indicated that the patriarchy system which found in the novel ‘The Tenant of Wildfell Hall’ (1848) touch some basic institution namely economic institution, education, religion, family, state institution and cultural values. This novel told us about the condition of society in the Victorian era especially related to the patriarchy system occurred in that era.